The Effect of Commercial Bank Lending Interest Rate on the Performance of the Residential Property Market in Kenya - Charles Gitiya Njoroge; Willy M. Muturi; Oluoch Oluoch (European Scientific Journal, ESJ, 2019)
The purpose of the study was to establish the effect of commercial bank lending interest rates on the performance of the residential property market in Kenya. Swelling of the residential property prices in Kenya vis a vis the commercial bank lending interest rates has ignited concerns about the sustainability of residential property market in Kenya. This study adopted a positivist philosophical attitude using causal research design. The study used secondary data from first quarter of 2005 to fourth quarter of 2018. The study conducted several test statistics and diagnostic tests in order to achieve the most optimal solution. Vector error correction model and auto-regressive distributed lag model were employed to test the hypothesis in the short run and long run respectively. The results found out that commercial bank lending interest rate had a negative effect on performance of residential properties in Kenya in both the short run and long run in line with loanable fund theory. The study has narrowed down the research gap brought about by the conflicting emprirical, theoretical and conceptual literature with regard to the effect of commercial bank lending interest rate on performance of residential property market in Kenya. To investor, the study recommends that need to negotiate for favorable loan terms especially interest rate given to them and/or their potential customers as it ultimatly influences their returns in the residential property market in Kenya both in the short run and long run.